2010
DOI: 10.1080/15459620903582244
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Oil Mists Using a Semivolatile Aerosol Dichotomous Sampler

Abstract: The sampling performance of the semivolatile aerosol dichotomous sampler (SADS) was tested and compared with existing vapor and particle sampling methods: filtration, electrostatic precipitation, and vapor adsorption. Seven different test fluids were used to generate test droplets, and their concentrations and composition in each phase were evaluated using gas chromatography. The amount of wall loss inside the SADS was also evaluated. Combined vapor and particle concentrations for each test aerosol were not st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…(15,19,36,37) Volckens and Leith (38,39) later reported that electrostatic precipitators have the potential for chemical artifact formation, especially with chemicals containing double bonds in their structure. Reaction and degradation due to ozone and corona-related ions in ESPs has been reported in other literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(15,19,36,37) Volckens and Leith (38,39) later reported that electrostatic precipitators have the potential for chemical artifact formation, especially with chemicals containing double bonds in their structure. Reaction and degradation due to ozone and corona-related ions in ESPs has been reported in other literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory test of SADS using oil mist, the sampling media were charcoal tubes which can be connected almost directly to the outlets of SADS using a short Tygon tubing. (19) Due to the wide opening of the OVS tube, some extra interface between the tube and SADS is inevitable. A male piece of a quick disconnect couplings was inserted into the inlet of an OVS tube and then a short 114-inch Tygon tubing connected between SADS and the disconnect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations